Extensive IgE Cross-Reactivity towards the Pooideae Grasses Substantiated for a Large Number of Grass-Pollen-Sensitized Subjects - Johansen, Niels; Weber, Richard W.; Ipsen, Henrik; Barber, Domingo; Broge, Louise; Hejl, Charlotte (International archives of allergy and immunology, 2009)
Background: Allergy to taxonomically related species is a common phenomenon caused by the same immunological receptor cross-reacting to homologous allergens from different species. Knowledge of patterns of cross-reactivity is crucial for the selection of optimal products for diagnosis and for specific immunotherapy. The objective of this study was to investigate patterns of serum IgE cross-reactivity towards pollens from various grass species. Methods: With grass group 1 allergens as the representative group, amino acid sequence alignment, structural modelling and comparison of 3D surface characteristics were performed to exemplify the molecular basis of IgE cross-reactivity. IgE binding to extracts from ten different grass species was determined (total number of data pairs >19,000), and IgE inhibition experiments using Phleum pratense were performed. Results: Analysis of surface topography for group 1 grass allergens demonstrated ample space for IgE binding epitopes in surface areas conserved among Pooideae grasses. Significant correlation was observed between the serum IgE response to P. pratense extract and extracts from the other Pooideae grasses analyzed. P. pratense extract was demonstrated to inhibit the binding of IgE to the allergens in all of the extracts included in the investigation, indicating patient IgE to be primarily directed towards common epitopes. Conclusion: Extensive IgE cross-reactivity was observed towards the allergens of the Pooideae grasses, meaning that the immune system does not appear to distinguish based on the IgE level between the different species of this subfamily. The data suggest equal effect upon use of any of the Pooideae species for diagnostic as well as therapeutic purposes.